Functional MRI of migraine - Schwedt, Todd J; Chiang, Chia-Chun; Chong, Catherine D; Dodick, David W (Lancet neurology, 2015)
Migraine is a disabling neurological condition manifesting with attacks of headache, hypersensitivities to visual, auditory, olfactory and somatosensory stimuli, nausea, and vomiting. Exposure to sensory stimuli, such as odours, visual stimuli, and sounds, commonly triggers migraine attacks, and hypersensitivities to sensory stimuli are prominent during migraine attacks, but can persist with less magnitude between attacks. Functional MRI (fMRI) has been used to investigate the mechanisms that lead to migraine sensory hypersensitivities by measuring brain responses to visual, olfactory, and painful cutaneous stimulation, and functional connectivity analyses have investigated the functional organisation of specific brain regions and networks responsible for sensory processing. These studies have consistently shown atypical brain responses to sensory stimuli, absence of the normal habituating response between attacks, and atypical functional connectivity of sensory processing regions. Identification of the mechanisms that lead to migraine sensory hypersensitivities and that trigger migraine attacks in response to sensory stimuli might help to better understand neural dysfunction in migraine and provide new targets for migraine prevention, and could provide fMRI biomarkers that indicate early responses to preventive therapy.